Pendeteksi Tingkat Kebisingan berbasis Internet of Things sebagai Media Kontrol Kenyamanan Ruangan Perpustakaan - Hidayat, Arif Dwi; Sudibya, Bambang; Waluyo, Catur Budi (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The library is a place that is used as a study and reading room, so that a comfortable place is needed from disturbances in the library building. Based on the decision of the Minister of Environment in 1996, the standard noise for library environments ranged from 45 to 55 dB. but in fact there is often a commotion caused by visitors. in this study a noise level detection system was created where the noise detection system is expected to be used as a media for comfort control in the library room. The noise level detector uses a sound sensor that is connected to Arduino.The system will be equipped with a warning system in the form of Buzzer and Warning Text sounds that will be displayed on the P10 LED Panel and equipped with Internet of Things technology that allows the supervisor or guard of the library to monitor the noise of the library room real time via Web Server. The test results show that this tool can detect noise levels in the range of at least 41 dB and a maximum of 69 dB with a deviation of 0.6 and an average error of 1.0%. the average sound intensity measured in the library room is 56.24 dB. The average percentage of the success of the system against Buzzer and Warning text warnings is equal to 97.3% and the average percentage of the success of sending data to the web server in the noise level detector is 95%